2010
DOI: 10.1021/jp101231c
|View full text |Cite
|
Sign up to set email alerts
|

Optical Properties of Au, Ag, and Bimetallic Au on Ag Nanohole Arrays

Abstract: A systematic study of the optical properties and analytical response is reported for gold and silver nanohole arrays with different hole diameters with a fixed periodicity of 450 nm. Nanosphere lithography in combination with oxygen plasma etching has been used to fabricate the nanohole arrays. The plasmonic response of nanohole arrays is characterized in transmission spectroscopy (λ = 500−1000 nm spectral region), which varied with the metal composition and diameter of the nanoholes. The sensitivity to bulk r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
77
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 55 publications
2
77
1
Order By: Relevance
“…When the two holes overlap, two sharp apexes are created and act as an optical antenna that focuses the electromagnetic field to very small region at the sharp apexes [178]. Murray-Méthot and coworkers [179] recently investigated the optical properties and analytical response such as sensitivity, transmission intensity, and FWHM of various arrays. Ag and Au arrays with different periodicities, diameters and bimetallic nanoholes were examined.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…When the two holes overlap, two sharp apexes are created and act as an optical antenna that focuses the electromagnetic field to very small region at the sharp apexes [178]. Murray-Méthot and coworkers [179] recently investigated the optical properties and analytical response such as sensitivity, transmission intensity, and FWHM of various arrays. Ag and Au arrays with different periodicities, diameters and bimetallic nanoholes were examined.…”
Section: Laser and Photonics Reviewsmentioning
confidence: 99%
“…Recently, it was also demonstrated that the intensity of enhanced transmission in nanohole arrays was improved for bimetallic films, using a Ag underlayer and a Au overlayer. 14 Other examples include FON substrates composed of Au multilayers with silver oxide island films. 35 The authors demonstrated that the films are more stable to oxidation and they have an improved Raman response.…”
Section: Effect Of the Metal Film Composition On Raman Amplificationmentioning
confidence: 99%
“…7 Nanohole arrays offer great promise for various applications, including theoretical investigation of light-surface plasmon interactions, 1 biosensing, 8,9 plasmon-enhanced photovoltaics, 10 spectro-electrochemistry, 11 and surface enhanced spectroscopy. 12,13 The optical properties of nanohole arrays are well understood for different hole diameters, 14 periodicities, 15 and metal compositions. 14 However, grating coupling conditions remain poorly characterized and uncertainty remains concerning the importance of symmetry (S, rotation symmetry of 60 for hexagonal arrays), incidence angle (q) and azimuthal rotation (f) for sensing and optical ltering.…”
Section: Introductionmentioning
confidence: 99%